EXPERIENCE OF USAGE OF ADAPTED GOAT MILK FORMULA IN NUTRITION OF HEALTHY INFANTS DURING FIRST SIX MONTHS OF LIFE - T. E. Borovik; O. L. Lukoyanova; N. N. Semenova; N. G. Zvonkova; T. V. Bushueva; T. N. Slepanova; E. A. Kopyl’tsova; O. S. Mel’nichuk (Вопросы современной педиатрии, 2014)
Background: The authors had a goal to assess clinical efficacy of adapted goat milk formula and its possibilities for usage in nutrition of infants during first six months of life. Patients and methods: Seventy three healthy infants at the age from 1 to 4 months were followed-up, among them 42 — on artificial feeding and received the investigated formula, and 31 — breast-fed (comparative group). The duration of follow-up was 30–40 days. The criteria of efficacy of the investigated formula were: tolerability, dynamics of weight and height and laboratory characteristics (hemoglobin concentration in erythrocytes and equivalent of hemoglobin in reticulocytes, concentrations of blood iron, ferritin, prealbumin, active metabolites of vitamin D3 (25OH) in capillary blood, revealing of specific immunoglobulins E to cow and goat milk proteins with the help of express-method and coprological test), assessment of actual nutrition of infants with calculation of the main macro- and micronutrients, energetic value of the diet and protein efficacy coefficient. Results: The investigated children adapted goat milk formula meets all the modern criteria according to the composition of such type of food products, provides physiological demands of infants in the main nutrients and energy, maintains their normal physical development and normalizes stool in tendency to constipations. Conclusion: The investigated milk formula can be used in nutrition of non-breastfed infants during first 6 months of life.